Sedimentary Petrology Implications in Petroleum Industry - Ismail Al-Juboury, Ali (IntechOpen, 2022)
Sedimentary Petrology - Implications in Petroleum Industry provides some new information on the importance of sedimentary petrology in various disciplines that are of great significance for the evaluation and locating of oil and gas. This book focuses on the provenance history of clastic rocks, reservoir characterization and hydrocarbon exploration in carbonate reservoirs, and enhanced oil recovery based on data from petrological investigations from various regions in Asia and Europe.